Development of a Preliminary Question Prompt List as a Communication Tool for Adults With Gastroesophageal Reflux Disease: A Modified Delphi Study. Issue 10 (November 2020) - Kamal, Afrin; Katzka, David A.; Achkar, Edgar; Carlson, Dustin; Clarke, John; Fass, Ronnie; Gyawali, Chandra P.; Patel, Dhyanesh; Penagini, Roberto; Rezaie, Ali; Roman, Sabine; Savarino, Edoardo; et al.
Abstract : Background: Question prompt lists (QPLs) are structured sets of disease-specific questions intended for patient use, encouraging patients to ask questions to facilitate their consultation with their physician. Aim: The aim of this study was to develop a QPL specific to adults with gastroesophageal reflux disease (GERD), created by esophageal experts. Methods: The QPL content (78 questions) was derived through a modified Delphi method consisting of 2 rounds. In round 1, 18 esophageal experts provided 5 answers to the prompt "What you wish your patients would ask" and "What questions do patients often not ask, that I wish they would ask?" In round 2, the experts rated each question on a 5-point Likert scale, and responses rated as "essential" or "important, " determined by an a priori threshold of ≥4.0, were accepted for the QPL. Results: Twelve esophageal experts participated. Of 143 questions from round 1, 110 (76.9%) were accepted for inclusion in the QPL, meeting a median value of ≥4.0, and, subsequently, it reduced to 78, minimizing redundancy. Median values ranged between 4.0 and 5.0, with the highest agreement median (5.0) for questions asking dosing and timing of proton pump inhibitor therapy, and surveillance in Barrett's. Questions were categorized into the following categories: "What does this illness mean, " "lifestyle modifications, " "general treatment, " "treatment with proton pump inhibitors, " "What I should expect for my future, " and "Barrett's." The largest number of questions covered lifestyle modifications (21.8%), with the highest agreement median (5.0) for "How helpful are lifestyle modifications in GERD?" Conclusions: A preliminary GERD-specific QPL, the first of its kind, was developed by esophageal experts. Modification after more patient consultation and feedback is planned in subsequent versions to create a GERD-QPL for eventual use in clinical gastroenterology. Abstract : Supplemental Digital Content is available in the text.